PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA UD. JUGLE DI SITUBONDO DENGAN MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING - Aqidah, Lailatul; Kusnadi, Edy; Wiryaningtyas, Dwi Perwitasari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing management is the process of all exchange activities with the aim of obtaining profits and also satisfaction for consumers. The company will achieve good goals if the business undertaken is in accordance with the predetermined marketing strategy. The purpose of this study was to analyze and test the effect of marketing strategy on increasing product sales at UD. JUGLE. The population in this study were all UD consumers. JUGLE which is located in Situbondo Regency. The sampling technique used is a probability sampling technique with a simple random sampling method. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 (Partial Least Square) application with the Structural Equation Model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product quality has a significant positive effect on consumer buying interest, product quality has a positive but not significant effect on purchasing decisions, promotions have a significant effect on consumer buying interest, promotions have a significant effect on purchasing decisions, interest consumer buying has a significant effect on purchasing decisions. The results of the indirect effect hypothesis test show that product quality has a significant effect on purchasing decisions through consumer buying interest, promotions have a significant effect on purchasing decisions through consumer buying interest.